A Case Report of Cervicitis Gonorrhea - Diah Mira Indramaya; Zahruddin Ahmad; Septiana Widyantari (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Gonorrhea refers to a set of clinical conditions involving infection with the sexually acquired bacterial pathogen, Neisseria gonorrhoeae. One of the simplest gonococcal infections in women involves mucosal surfaces of the endocervix that cause cervicitis, a frequently asymptomatic inflammatory condition that results in an abnormal mucopurulent discharge and cervical friability. Purpose: To report a case of cervicitis gonorrhea in a female patient whose sexual partner had a hisstory of unprotected promiscuous intercource with multiple sex worker. Case: A 24-year-old female patient presented with increased vaginal discharge for 4 days. Her husband had a history of having sexual intercourse with a sex worker 8 days before. Physical examination revealed mucopurulent exudate in the genitalia and endocervical canal. The Gram staining showed numerous leucocytes and Gram-negative intracellular diplococci, while the result of polymerase chain reaction (PCR) examination for Chlamydia trachomatis was negative. The patient was treated with single-dose cefixime 400 mg orally and doxycycline 100 mg orally twice a day for 7 days. Discussion: The present case report showed cervicitis gonorrhea co-infected with a nonspecific genital infection that was felt asymptomatic and unintentionally found when the patient accompanied her husband to Sexually Transmitted Infection (STI) clinic. The presumptive treatment of cervicitis directed against N. gonorrhoeae and C. trachomatis in this patient leads to a complete cure of the disease. Conclusion: It is important to treat the sexual partner of a patient with urethritis gonorrhea. The empiric treatment of cervicitis that is directed against N. gonorrhoeae and also against C. trachomatis is mandatory in preventing further possible complications.